PWE-109 A feasibility study of adjuvant statin therapy in the prevention of post-operative recurrence of oesophageal adenocarcinoma (the stat-roc feasibility study). (17th June 2017) - Alexandre, L; Clark, A; Walton, S; Lewis, MP; Kumar, B; Cheong, E; Warren, H; Kadirkamanathan, S; Parsons, S; Dresner, S; Loke, Y; Swart, AM; et al.
Abstract : Introduction: Preclinical studies have demonstrated statins inhibit proliferation, promote apoptosis and limit invasiveness of oesophageal adenocarcinoma (OAC) cell lines. Observational research has demonstrated significant improvements in mortality associated with statin use after diagnosis of OAC. We aimed to determine the feasibility of assessing adjuvant statin therapy in patients with operable OAC in a phase III randomised controlled trial. Method: For this multi-centre, double-blind, parallel group, randomised, placebo-controlled trial, eligible patients were adults with OAC or Siewert type I/II adenocarcinoma due surgery. Participants were recruited from four UK centres and randomly assigned (1:1) to simvastatin 40 mg or matching placebo by block randomisation, stratified by centre. Participants, clinicians and investigators were blinded to treatment allocation. Treatment started from the date of discharge following surgery and continued for up to one year. Feasibility assessments of recruitment, retention, drug absorption, adherence, safety, quality of life, generalisability, all-cause and disease-free survival were made. Trial registration: ISRCTN98060456 . Results: Between 23rd November 2014 and 22nd July 2016, 120 patients were assessed for eligibility, of which 32 (26.7%) were randomised. Of patients meeting eligibility criteria, 59.3% (32/54) were randomised. Patients allocated to simvastatin had significantly lower LDL cholesterol levels by three months (adjusted mean difference, −0.83 mmol/L, 95% CI −1.4 to −0.22, p=0.009). Median medication adherence for the preceding three months of follow-up at 3, 6, 9 and 12 months, respectively, was 83%, 94%, 99%, and 94%, with no significant differences in adherence between treatment groups. In total, 87.5% in the simvastatin group and 92.9% in the placebo group (p=0.626) experienced at least one adverse event. Completion of quality of life data was high (98.3% of questionnaire items) with no clinically significant differences observed between treatment groups. Cardiovascular disease (p=0.003), diabetes (p=0.003) and aspirin use (p=0.01) were more prevalent in the non-randomised group compared with the randomised group. There were no significant differences between groups for overall (p=0.716) or disease-free survival (p=0.807). Conclusion: This RCT supports the feasibility of assessing adjuvant statin therapy in a future phase III trial in patients with operable OAC. Disclosure of Interest: None Declared